APPLICATION OF LEXICAL CHUNK THEORY IN TEACHING CHINESE AS A FOREIGN LANGUAGE (SCIENCE TIME JOURNAL, 2026)
The theory of lexical chunks first emerged in the process of learning and teaching English and later became one of the most effective approaches in language acquisition. This article examines how lexical chunks can be applied in teaching Chinese to foreigners. Lexical chunks are prefabricated word combinations that help learners produce speech more quickly and naturally. Although this approach is widely used in English language teaching today, it has only recently begun to be introduced into Chinese language instruction. It should be noted that the implementation of chunk-based teaching methods can improve the quality of Chinese language education.